Standarisasi Nusyuz Istri: Analisis Komparatif Empat Mazhab Fikih - Fashihuddin Arafat; Mohamad Afif Mubarok (MASADIR: Jurnal Hukum Islam, 2026)
This study is grounded in the phenomenon of wife’s nusy?z (disobedience), which frequently triggers domestic conflict due to ambiguity in its definition and indicators, often producing subjective interpretations that may harm a wife’s rights or a husband’s legal certainty. This study aims to comparatively analyze the indicators and handling procedures of wife’s nusy?z according to the Hanafi, Maliki, Shafi‘i, and Hanbali schools, and to formulate an objective standardization for contemporary family law. This is a normative legal study using a library-based method with conceptual and comparative approaches. Primary data were drawn from the authoritative (mu‘tamad) texts of each school and analyzed descriptively and comparatively. The findings show that all four schools agree that refusal of marital intimacy (tamk?n) and leaving the marital home without permission constitute core indicators of nusy?z, while differing on thresholds: the Shafi‘i and Hanbali schools recognize psychological behavioral change (at-taghayyur) as an early indicator, the Hanafi school requires concrete physical evidence, and the Maliki school extends the indicators to personal religious obligations. Regarding handling procedures, all four schools agree on a graduated principle (at-tart?b) beginning with admonition, hajru (separation), and non-injurious corrective measures, differing technically in the duration of hajru and the authority of the ?akam (arbitrator). This study contributes an objective, humane, and measurable reconstruction of nusy?z standardization to secure legal certainty while protecting wives’ rights.